Análise de potência óptica e o modelo de distribuição de conexões entre os terminais de uma rede de fibra óptica - DANTAS, Vitor Gabriel Mendes (2022)
Due to the pandemic of Covid-19, many services were migrated to the internet in order to meet the demand respecting social detachment. Therefore, high-capacity data transmission networks become increasingly necessary, and this occurs as in times past with other situations. In this context, this course completion work addresses the construction of passive fiber optic networks, explaining how the distribution of connections to the worldwide network of computers occurs from them. Among the subject guidelines, it will also be explained the benefits of using the fiber optic transmission line, the obstacles that are faced by internet providers and how they can be avoided from an analytical mapping.